The international law of disaster relief - Caron, David D.; Kelly, Michael J., 1968-; Telesetky, Anastasia (New York : Cambridge University Press, 2014)
'This edited volume analyzes the evolution of international disaster law as a field that encompasses new ideas about human rights, sovereignty, and technology'--
Machine generated contents note: Part I. The Legal Theory of International Disaster Relief: 1. International law and the disaster cycle Daniel A. Farber; 2. Natural disasters and the theory of international law Toshiya Ueki; 3. International disaster relief law and article 38(1)(c) of the statute of the international court of justice: the forgotten source of international law Imogen Saunders; 4. Evolution of international disaster response law: towards codification and progressive development of the law Emika Tokunaga; Part II. The Law of International Disaster Relief: From Local to Global: 5. International disaster response laws, rules, and principles: a pragmatic approach to strengthening international disaster response mechanisms Claire Clement; 6. Release of radioactive substances into the sea and international law: the Japanese experience in the course of nuclear disaster Yukari Takamura; 7. The international law of ninety-six hours: urban search and rescue teams and the current state of international disaster response law Kirsten Nakjavani Bookmiller; Part III. The Right of Access to International Disaster Relief: 8. Legal framework applicable to humanitarian actors responding to disasters in weak and fragile states Catherine Gribbin and Ilario Maiolo; 9. Disasters, despots, and gun-boat diplomacy Catherine Shanahan Renshaw; 10. Hunger without frontiers: the right to food and state obligations to migrants Katie Sykes; 11. Disasters, international law, and persons with disabilities Akiko Ito; Part IV. Disaster Prevention and Relief: Anticipatory Responses from State Actors: 12. Help from above: the role of international law in facilitating the use of outer space for disaster management Brian R. Israel; 13. Utilizing international climate-change-adaptation funding to reduce risks of natural disasters in the developing world Paul Govind; 14. Challenges to state sovereignty in the provision of international natural disaster relief Amelia Telec; Part V. Disaster Prevention and Relief: Anticipatory Responses from NGOs: 15. The role of international organizations in disaster response: a case study of recent earthquakes in Japan Kentaro Nishimoto; 16. International investment law and disasters: necessity, peoples, and the burden of (economic) emergencies Ibironke T. Odumosu-Ayanu; 17. Clarifying the acquis humanitaire: a transnational legal perspective on the internalization of humanitarian norms Dug Cubie.
Keywords: Disaster relief -- Law and legislation; Emergency management -- Law and legislation